Sectoral Impacts of Crude Oil Price Movements on Stock Markets: Evidences from Selected Emerging Market Economies - Wada, Isah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This thesis investigates the impacts of Brent crude oil price shocks on sector returns in selected net crude oil exporting and importing emerging market countries. The data includes stock market returns on a Wednesday to Wednesday market trading days. This helps to remove cross-country time differences and to capture day-of-the-week effects. The sample period spans from 2003-2016, 2005-2016 and 2007-2016 depending on the availability of data for various sectors for selected countries namely––Saudi Arabia, The United Arab Emirates (UAE), China and India categorized as crude oil exporting and importing countries, respectively. The selected sector returns are––the banking and financial services sector returns, the agriculture or food/consumer durable sector returns and the construction/industrial sector returns. The VIX index reported by the Chicago Board of Option Exchange (CBOE) is also included as an indicator of investor sentiment about the financial markets, another global factor affecting stock markets in addition to Brent crude oil price changes. A regime switching approach is considered for two regimes as stable with high mean low variance and as recession with low mean high variance regimes with both fixed and time-varying transition probabilities. The estimates of the Markov-switching dynamic regression (MS-DR) model with fixed smoothed transition probabilities support a dynamic non-linear relationship betwen stock returns and crude oil price changes with two regimes. Probabilities to stay in each regime are close to 1 indicating persistence of the regimes. Regarding the net crude oil-exporting countries, Saudi Arabia and UAE, the evidence shows that, in general, both the positive and negative crude oil price shocks have positive impacts on the sector returns during the stable regime but no significant effect during the recession regime. Yet, an asymmetric oil price effect is observed such that both positive and negative oil price shocks have positive impact on all sectors in the stable regime but with a greater magnitude of the negative shock. Regarding the net oil importing countries, oil price rises are positively related with all sector returns during stable regime except that of consumer durables in India. While oil price falls positively affect the Indian banking and construction sectors during stable regime, they are of same magnitude as the positive oil price shocks during the same regime indicating no asymmetric effect. However, the asymmetric effect is observed for the case of China. The oil price falls, in general, has no significant effect on any sector returns during recession regime for the case of oil importing countries. The positive influences of oil price rises, at least in the short-run, during stable regime may be interpreted as arising from the demand side oil price shocks rather than supply disruptions. The VIX index, in general, has highly significant negative relationship with all sector returns in both oil exporting and importing countries during the stable regime. Relaxing the fixed transition probabilities indicate that rises in oil prices and VIX index significantly decreases the probability of staying in stable regime in Saudi Arabia and in China.

ÖZ: Tezde, örneklenen net ham petrol ihracatçı ve ithalatçı ülkelerin sektör bazındaki hisse senedi getirileri üzerindeki Brent ham petrol fiyat değişimlerinin etkileri incelenmektedir. Kullanılan veriler, is günü baz alınarak Çarşamba’dan Çarşamba’ya haftalık değişimler olarak hesaplanmıştır. Böylelikle, analiz sırasında, ülkeler arasındaki zaman farklılıkları ile haftanın günlük etkilerinin sorun olmaması sağlanmaktadır. Çalışmanın zaman boyutu, ülkelerin sektörler itibariyle mevcut olan zaman serilerinin sürelerine göre tespit edilmiş olup 2003-2016, 2005-2016 ile 2007-2016 arasında yer almaktadır. alışmda, net ham petrol ihracatçısı olarak Suudi Arabistan ile Birleşik Arap Emirlikleri ve net petrol ithalatçısı olarak ise Çin Halk Cumhuriyeti ile Hindistan örneklenen ülkeler arasında yer almaktadır. Her ülke için, genel olarak, bankacılık ve veya finans servis sektörü, tarım veya gıda snayı ve inşaat/dayanıklı tüketim malları/sanayi sektörleri incelenmektedir. Hisse senedi piyasaları ile petrol fiyatlarını etkileyen küresel etken olarak, yatırımcı beklentilerini yansıtmakta olan ve “Chicago Board of Option Exchange” tarafından yayımlanan VIX endeksi ise ekonometrik modelde kontrol değişkeni olarak kullanılmıştır. Temel analiz aracı olarak ise, iki rejimli (genişleme ve daralma) Markov Rejim değişimi yaklaşımı kullanılmıştır. Sabit probabilite varsayımı altındaki Markov-değişim dinamik regresyon (MS-DR) modeline ait bulgular, ham petrol fiyat değişimleri ile sektörel hisse senedi getirileri arasındaki ilişkinin doğrusal olmadığını ortaya koymuştur. Ayrıca rejim değişim olasıklarının 1’e yakın olması heriki rejimin de süreklilik gösterdiğine işaret etmektedir. Petrol ihracatçısı ülkeler için elde edilen sonuçlara göre, petrol fiyatlarındaki artış ve düşüşler, sektörel hisse getirilerini genişleyen rejimde olumlu etkilerken daralan rejimde statistiksel olarak anlamlı bulunmamaktadır. Ayrıca, petrol fiyat şokunda asimetrik etki de gözlenmekte, şöyleki petrol fiyat düşüşlerinin fiyat artışlarına göreli olarak olumlu etkisinin daha fazla olduğu görülmektedir. Net petrol ithalatçısı ülkelerde ise, genişleyen rejimde, petrol fiyat artışları tüm sektör getirilerini pozitif yönde etkilemektedir. Ancak, negative petrol şoku, genişleyen rejimde Hindistan’da bankacılık ve inşaat sektörlerini olumlu yönde etkilerken bu etkinin pozitif petrol şoku ile aynı değerde olması petrol artış ve düşüşlerinin Hindistan’da sözkonusu sektörlerde asimetrik etki yaratmadığına işaret etmektedir. Diğer yandan, negative petrol fiyat şoklarının daralan rejimde petrol ithalatçısı olan ülkelerde etkili olmadığı görülmektedir. Genel olarak, tüm ülkelerde pozitif petrol fiyat şoklarının hisse senedi getirilerini genişleyen rejimde, en azından kısa dönemde, olumlu etkilemesi şöyle açıklanabilir; petrol fiyat artışları arz yönlü olmayıp, talep yönlü olması nedeniyle. VIX index artışları ise,genişleyen rejimde tüm ülkelerde, tüm sektörleri anlamlı olarak negative yönde etkilemektedir. Petrol fiyat artışları ile VIX endeks değişimlerinin Suudi Arabistan ve Çin’de rejim değişim probabilitesini negative etkilediği elde edilen diğer bulgular arasında yer almaktadır.
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2017. Supervisor: Assoc. Prof. Dr. Gülcay Tuna Payaslıoğlu.
Keywords: Economics; Power resources--Oil--Economic aspects--Stock Market; Oil price shocks; sectoral stock market returns; Markov-switching dynamic regression; time-varying smoothed transition probabilities